Study of Prediction Simulation Life Storage to Determine the Quality of Mangosteen (Garcinia mangostana L.) - Sihombing, Yennita - (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2015)
Demand for mangosteen fruits (Garciana mangostana L) is currently increasing both for local and export markets. Quality of mangosteen fruit has been kept until now, even increased by efforts of post-harvest handling. The problem on postharvest of mangosteen is mainly on storage process. The quality of mangosteen is affected by the temperature condition during storage period. Waxing is usually used for fruits to extend their shelf life. In this study, combination of waxing and low temperature storage were studied to obtain the optimum storage condition for mangosteen. The objectives of this study were to determine the effect of combination of waxing and low temperature storage on the quality changes of mangosteen. It was shown that storage of mangosteen with waxing treatment of 5% and temperature storage of 8oC resulted the longest period of storage, i.e., 39 days. At this condition, the firmness was 2.00 kgf, total soluble solid was 16.10oBrix, and respiration rate of CO2 was 1.67ml/kg hr. In this study, prediction of storage life of mangosteen was carried out based on the firmness which accepted by panelist from organoleptic test. It is shown that waxing concentration 0% and temperature storage 8oC effectiveness to storage life until 16 days.